Using the Theory of Reasoned Action and Self-Efficacy to Explore Nursing Students’ Spiritual Health Promotion - Si-Chi Chen, Fu-Ju Tsai, Gwo-Liang Yeh, Yih-Jin Hu, Chie-Chien Tseng, (International Journal of Innovative Research in Medical Science, 2017)
Purpose: The purpose of this study was to apply the theory of reasoned action and self-efficacy in order to explore nursing students’ behavioral intention and predict its effects on the practice of spiritual health promotion. Design: An exploratory research design was adopted. Methods: In total, 191 5th-year nursing students participated in the curriculum on professional care. A self-reported open-ended questionnaire was used to collect the data. Both investigator triangulation and content analysis were used for the data analysis. Results: The results of this study showed that 75% of all of the themes represented nursing student’s behavioral beliefs, normative beliefs, and self-efficacy to predict the effect of behavioral intention on the practice of spiritual health promotion. Conclusions: Following the results of this study, the aim is to build a structured questionnaire including items on behavioral beliefs, evaluations of behavioral outcomes, normative beliefs, motivation to comply, attitudes, subjective norms, self-efficacy, and behavioral intention to survey nursing students on the practice of spiritual health promotion in the future. Clinical Relevance: In further studies, nursing students will be surveyed on their behavioral attitudes, subjective norms, and self-efficacy to predict the effect of their behavioral intention on the practice of spiritual health promotion. Furthermore, nursing students may increase their self-reported levels of physical, psychological, spiritual, and social health promotion to help clinical patients.